Compostos bioativos, atividade antioxidante e características físico-químicas de mel de Apis mellifera da região Oeste do Paraná - Ribeiro , Renato de Jesus (2021)
As the main bee food known worldwide, honey is considered a complete food and one of the purest foods found in nature, having great importance in the maintenance of our body. The objective of this work was to evaluate the physicochemical characteristics of honey and bioactive compounds, to characterize the quality of honey from lakeside municipalities in Itaipu and far from the lake, in the western region of Paraná. Sixty-six honey samples were analyzed from October 2018 to August 2019. The physicochemical parameters evaluated were: color, moisture, hydroxymethylfurfural, pH and free acidity, all in accordance with national and international standards, with values means 0.36 nm, 18.8%, 10.34 mg.kg -1, 4.01 and 17.36 meq.kg -1, respectively. Bioactive compounds and antioxidant activity were also analyzed, with mean values of 16.34 mgGAE.100 g-1 for Total Phenols, 21.35 mgEQ.100 g-1 for Flavonoids and 0.09µmol ET. g-1 for DPPH. When comparing the honey samples from the lakeside and far from the lake regions, there was a difference only for HMF, acidity and total phenols. It is concluded that the honey from the western region of Paraná has similarity in its composition and characteristics and its good quality is proven, also indicating the standardization by beekeepers in the production of this food. In addition, the analyzed honey samples showed good results for the levels of bioactive compounds.